135k views
1 vote
The table shows the function ​ g(x) ​ . Select from the drop-down menu to correctly compare the growth factors for the exponential functions g(x) and f(x)=4(3)x .

x: 0, 1, 2
g(x): 3, 12, 48

Is the growth factor greater than, lesser than, or equal to the growth factor of g(x)?

User PawelP
by
5.9k points

2 Answers

5 votes

Answer:

f(x) is less than the growth factor of g(x).

Explanation:

User Roohul
by
5.5k points
4 votes

Answer:

The growth factor of f(x) is less than the growth factor of g(x).

Explanation:

The general form of exponential function is


h(x)=ab^x

Where, a is the initial value and b is the growth factor.

The given function is


f(x)=4(3)^x

The initial value of f(x) is 4 and the growth factor is 3.

From the given table it is noticed that the function g(x) is passing through the points (0,3), (1,12), (2,48).


3=ab^0


a=3


12=3(b)^1


b=(12)/(3)=4


g(x)=3(4)^x

The initial value of g(x) is 3 and the growth factor is 4.

Therefore the growth factor of f(x) is less than the growth factor of g(x).

User Joe Dixon
by
6.4k points